RNA turnover in bacteria, archaea and organelles - Maquat, Lynne; Arraiano, Cecilia M. (Cecilia Maria), 1959- (Methods in enzymology, 2008)
Specific complexes of protein and RNA carry out many essential biological functions, including RNA processing, RNA turnover, RNA folding, as well as the translation of genetic information from mRNA into protein sequences. Messenger RNA (mRNA) decay is now emerging as an important control point and a major contributor to gene expression. Continuing identification of the protein factors and cofactors, and mRNA instability elements, responsible for mRNA decay allow researchers to build a comprehensive picture of the highly orchestrated processes involved in mRNA decay and its regulation. Covers the difference in processing of mRNA between eukaryotes, bacteria and archea. Benefit: Processing of mRNA differs greatly between eukaryotes, bacteria and archea and this affords researchers readily reproducible techniques to understand and study the molecular pathogenesis of disease. Expert researchers introduce the most advanced technologies and techniques to identify mRNA processing, transport, localization and turnover which are central to the process of gene expression. Benefit: Keeps MIE buyers and online subscribers up-to-date with the latest research Offers step by step lab instructions including necessary equipment and reagents. Benefit: Provides tried and tested techniques which eliminate searching through many different sources. Tested techniques are trustworthy and avoid pitfalls so the same mistakes are not made over and over.